Performance Enhancement of Ofdm-Based Systems Using Improved Parametric Linear Combination Pulses - Soto-Gomez, J (Springer New York LLC, 2015)
As the demand for better performance increases in next-generation networks, such as 5G technologies, more efficient modulation techniques are required. In this work, we evaluate the performance of the improved parametric linear combination pulses (IPLCP) in orthogonal frequency division multiplexing (OFDM) based systems. OFDM-based systems are very sensitive to frequency offset errors, and are characterized by producing high peak-to-average power ratio (PAPR) values. The IPLCP is evaluated in terms of average inter-carrier interference power, average signal to interference power, PAPR, and bit error rate. Theoretical and numerical simulations show that the IPLCP pulse performs well in OFDM-based systems in comparison to other existing pulses. © 2015, Springer Science+Business Media New York.